PERENCANAAN LAPIS TAMBAH PERKERASAN PADA RUAS JALAN LAMBARO – BATAS PIDIE - Rizaldi Fachrun; Muhammad Isya; Sofyan M. Saleh (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Lambaro - Batas Pidie is a highway that located in Aceh Besar District, and has important function as a national highway. This highway is connecting from Aceh Besar District to Pidie District, started from Ingin Jaya District to Lembah Seulawah District. There is pavement damage that needs overlay activity in the highway, so the pavement is needed to maintain. This study is performed to find the overlay thick of pavement by using Falling Weight Deflectometer (FWD) and Benkelman Beam (BB) tools. Overlay thick design is based on Design of Overlay Thick of Flexible Pavement by Deflection Method (Pd T-05-2005-B). The segment of this study is in Jalan Lambaro - Batas Pidie highway, the data that taken is from the same point between FWD and BB. This is from STA 14+250 to STA 16+300. To design the overlay, this investigation need the testing result deflection of FWD and BB, then the value result is corrected. After the obtain corrected deflection value, the next process is calculating uniformty factor (FK), representative deflection (Dsbl ov), design deflection (Dstl ov), overlay thick (Ho), factor of overlay thickness (Fo), and corrected overlay thick (HT). The result of this study is the overlay thick from FWD and BB, it is 7 cm for FWD and 9 cm for BB. From the study result, the conclution is the FK value is under 30% and used overlay pavement is concrete asphalt layer with 2,000 MPa Resilient Modulus and minimum stability of Marshall Value is 800 kg.